Petalidium sesfonteinense (Acanthaceae), a new species from the Kaokoveld, Namibia - Swanepoel, Wessel; Manzitto-Tripp, Erin A. (Phytotaxa, 2022)
Petalidium sesfonteinense, previously most commonly confused with the widespread P. variabile, is here described as a new species. It is only known from the Sesfontein area in the Kaokoveld Centre of Endemism, northwestern Namibia, where it grows on hillsides and along ephemeral riverbeds. Diagnostic characters for P. sesfonteinense include the short, stout trunk on older plants, white bark that peels on the younger branches in long, narrow strips, dendritic trichomes on vegetative parts, flowers in short dichasia with acute oblanceolate bracts, flowers with externally glabrous corollas, corolla lobes that are pink, magenta, apricot or cream and with the two upper lobes connate towards the base and the lower lobe with two yellow spots near the base. A comparison of some of the more prominent morphological features to differentiate Petalidium sesfonteinense from close relatives is provided. Based on IUCN Red List categories and criteria, a conservation assessment of Least Concern (LC) is recommended for the new species.